2009
DOI: 10.1002/ajh.21543
|View full text |Cite
|
Sign up to set email alerts
|

Prodromal myeloproliferative neoplasms: The 2008 WHO classification

Abstract: The concept of prodromal chronic myeloproliferative neoplasms has been endorsed by the WHO classification implicating a stepwise evolution of disease. Histology of the bone marrow (BM) and borderline to mildly expressed clinical features play a pivotal role for diagnosing prefibrotic-early primary myelofibrosis. By lowering the platelet count for essential thrombocythemia and regarding BM morphology, early manifestations are tackled. Pre-polycythemic stages of polycythemia vera with a low hemoglobin level at o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 124 publications
(313 reference statements)
1
67
1
3
Order By: Relevance
“…It is also important to note that other JAK2/CALR/MPL mutated MPN (or myelodysplastic syndromes [MDS]/MPN) can mimic ET in their presentation; these include prefibrotic PMF [4,43] and refractory anemia with ring sideroblasts with marked thrombocytosis (RARS-T) [4,44]. Therefore, bone marrow examination is often necessary to make an accurate morphologic diagnosis of ET and distinguish it from other myeloid neoplasms, especially from prefibrotic PMF; megakaryocytes in ET are large and mature-appearing whereas those in prefibrotic PMF display abnormal maturation with hyperchromatic and irregularly folded nuclei [45]. A recent large international study confirmed the prognostic relevance of distinguishing ET from pre-fibrotic PMF [26].…”
Section: Diagnosismentioning
confidence: 99%
“…It is also important to note that other JAK2/CALR/MPL mutated MPN (or myelodysplastic syndromes [MDS]/MPN) can mimic ET in their presentation; these include prefibrotic PMF [4,43] and refractory anemia with ring sideroblasts with marked thrombocytosis (RARS-T) [4,44]. Therefore, bone marrow examination is often necessary to make an accurate morphologic diagnosis of ET and distinguish it from other myeloid neoplasms, especially from prefibrotic PMF; megakaryocytes in ET are large and mature-appearing whereas those in prefibrotic PMF display abnormal maturation with hyperchromatic and irregularly folded nuclei [45]. A recent large international study confirmed the prognostic relevance of distinguishing ET from pre-fibrotic PMF [26].…”
Section: Diagnosismentioning
confidence: 99%
“…In its most recent (2016) revision [54], the WHO document lists the presence of driver mutations as one of several major criteria in the diagnosis of PV, ET and PMF (Table I) [54]. However, these mutations lack specificity and are unable to distinguish ET from masked PV or prefibrotic PMF [55][56][57][58][59]. Accordingly, bone marrow morphology is now considered as another major criterion for the 2016 WHO diagnosis of all three MPN (Table I) [54].…”
Section: Advances In Diagnosticsmentioning
confidence: 99%
“…The diagnosis of post-PV or post-ET MF should adhere to criteria recently published by the International Working Group for MPN Research and Treatment (IWG-MRT) (Table IV) [12]. Peripheral blood leukoerythroblastosis (i.e., presence of nucleated red cells, immature granulocytes, and dacryocytes) is a typical but not invariable feature of PMF; prefibrotic PMF might not display overt leukoerythroblastosis [13]. Bone marrow fibrosis in PMF is usually associated with JAK2V617F or mutant CALR, or MPL, trisomy 9, or del(13q) [14,15].…”
Section: Diagnosismentioning
confidence: 99%